Human rights education and the hidden curriculum: Theoretical and practical considerations on the Brazilian school routine - Barrios Gonzales, Alia (2020)
This paper presents theoretical and practical considerations about human rights education (HRE), in the context of pedagogical activities of Brazilian Basic Education, considering its guidelines and the school’s social interactions/ relationships (hidden curriculum). Based on a sociocultural constructivist theoretical approach, we present the microgenetic analysis of school situations that emerged in a research carried out in a public educational institution in Brasília, Distrito Federal. In the context of a human rights activity, the challenges faced by the contemporary school in relation to the actual implementation of HRE arise. It is necessary to develop a participatory pedagogy that makes HRE a relevant element for the students, as well as a teacher formation anchored in the analysis of the pedagogical practices and the programmatic actions of the HRE.